Interaction between oxidative stress and antioxidant markers in elite female players following a soccer games - Andersson, H.; Karlsen, A.; Blomhoff, R.; Raastad, T.; Kadi, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Exhaustive exercise may produce an excessive amount of free radicals leading to oxidative stress. Under normal conditions, the production of free radicals is in a fine-tuned equilibrium with the antioxidant defence system (Blomhoff, 2005). During a soccer game the aerobic energy system is highly taxed and increased free radical production is expected. Thus, we aimed to investigate the interaction between biomarkers of oxidative stress and antioxidants levels in elite female soccer players in response to a 90-min game. Methods: Blood samples were taken from 16 field players (22±3 yrs, 167±5 cm, 64±2 kg, 54±3 ml•kg-1•min-1) before, immediately and 21 h after a 90-min game. Plasma oxidised glutathione (GSSG), the ratio of reduced to oxidised glutathione (GSH:GSSG) and lipid peroxidation measured by D-Roms test were used as biomarkers of oxidative stress. Plasma endogenous (uric acid, total glutathione-TGSH) and dietary antioxidants(á-tocopherol, ascorbic acid- AA, total carotenoids, and polyphenols) were analysed using liquid chromatography and the Folin-Ciocalteu method. The food intake was standardised for all players during the study and secured an optimal intake of macro nutrients. Results: Immediately after the game GSSG significantly increased, GSH:GSSG decreased and D-Roms levels were unchanged. Uric acid, TGSH, AA and á-tocopherol significantly increased immediately after the game whereas total polyphenols decreased and total carotenoids remained unchanged. GSSG and GSH:GSSG ratio returned to baseline at 21 h whereas D-Roms levels remained unchanged. Uric acid, TGSH and AA returned to baseline 21 hrs after the game. In contrast, total polyphenols remained significantly reduced whereas á- tocopherol remained elevated. Significant increases above baseline were observed in total carotenoids only at 21 h. Conclusion: A soccer game in elite female soccer players induced a transient increase in GSSG and reduction in GSH:GSSG ratio accompanied by a robust response of the antioxidant defence systems. The orchestrated endogenous and dietary antioxidant responses in well-trained players helped to prevent the occurrence of lipid peroxidation after a soccer game. These results differ from that observed following soccer games in males where increased lipid peroxidation occurred for several days following the game (Ascensao et al., 2008; Ispirlidis et al., 2008). The differences may be related to the antioxidant functions of the female hormone estrogens. Furthermore, as polyphenols are only found in the circulation and not stored in the tissue, we suggest that the reduction in polyphenols following the game may be used as a marker of increased free radical production.